Prestige Marketing through Cultural Semiotics: The Economic Construction of Luxury in Merak Ngibing Batik - Echy, desiqoriah; nissa agniya resmisari; Wilman Ramdani; Ria Nirwana (Jurnal Pendidikan Ekonomi, 2026)
This study examines how cultural semiotics construct luxury value in Merak Ngibing batik MSMEs in Garut, Indonesia. Batik is no longer viewed merely as a traditional cultural product, but also as a symbolic commodity associated with exclusivity, elegance, and prestige. This research employed a descriptive qualitative method using Roland Barthes’ semiotic approach, particularly denotation, connotation, and myth. The data were collected from digital promotional contents on Instagram and TikTok, including product photographs, captions, slogans, and branding elements. Semi-structured interviews with MSME owners and consumers were also conducted to strengthen the analysis. The findings reveal that luxury is strategically constructed through visual aesthetics, handcrafted representations, premium color symbolism, and prestige-oriented promotional language. These symbolic representations contribute to the formation of exclusivity perception and premium consumer value. In addition, digital marketing platforms play an important role in circulating luxury narratives and strengthening the economic positioning of batik products. This study highlights how local cultural symbols are transformed into strategic economic value through prestige marketing practices in the creative economy sector.